Influence of environmental factors on the spat recruitment of the eastern oyster (Crassostrea virginica) along a subtropical river estuary in the Gulf of Mexico - Isidro Otoniel Montelongo-Alfaro; Jorge Homero Rodríguez-Castro; Jaime Luis Rábago-Castro; Alberto Carlos Velázquez-Narváez; Filiberto Toledano-Toledano; Roberto Pérez-Castañeda; Alfonso Correa-Sandoval (PLoS ONE, 2026)
Oyster spat recruitment is a key process controlling the persistence of natural populations. However, the relative influence of environmental gradients on spat recruitment remains poorly understood in estuaries of the Gulf of Mexico, especially along the Mexican coast. The aim of this study was to analyze the influence of some environmental factors on the spat recruitment of the eastern oyster ( Crassostrea virginica ) along the subtropical estuary of the Soto la Marina River, Gulf of Mexico. Six sampling sites were selected along the estuary, ranging from 1 km (Site 1) up to 22.8 km (Site 6) from the river mouth. Monthly, samples (April 2020–March 2021) of oyster spat ( C. virginica ) were collected from each site using an artificial spat collector. Water temperature, salinity, dissolved oxygen, pH, and Secchi depth were measured at the same time as oyster spat were collected for each site. Spatial and seasonal variations in the number of oyster spat were evaluated using a generalized linear mixed model (GLMM). Additionally, the relationship between spat recruitment and environmental variables was assessed using multiple linear regression analyses. Salinity was the unique environmental variable with significant differences between sites, showing a decreasing gradient from the river mouth to the upstream locations. The mean density of oyster spat decreased significantly from Site 1 to Site 5; however, they were absent at Site 6. Salinity and temperature were the environmental factors that explained the spatio-temporal variation of spat recruitment, showing a positive relationship with spat density on the collectors. Since temperature did not show significant differences between sampling sites, salinity is considered the primary environmental condition influencing the spat recruitment along the estuary. These findings provide a basis for identifying optimal areas and periods for oyster spat collection, supporting efforts in oyster reef restoration and the development of oyster aquaculture.